2015
DOI: 10.1038/srep08460
|View full text |Cite
|
Sign up to set email alerts
|

Fermi Level shifting, Charge Transfer and Induced Magnetic Coupling at La0.7Ca0.3MnO3/LaNiO3 Interface

Abstract: A large magnetic coupling has been observed at the La0.7Ca0.3MnO3/LaNiO3 (LCMO/LNO) interface. The x-ray photoelectron spectroscopy (XPS) study results show that Fermi level continuously shifted across the LCMO/LNO interface in the interface region. In addition, the charge transfer between Mn and Ni ions of the type Mn3+ − Ni3+ → Mn4+ − Ni2+ with the oxygen vacancies are observed in the interface region. The intrinsic interfacial charge transfer can give rise to itinerant electrons, which results in a “shoulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 56 publications
10
45
0
Order By: Relevance
“…Self-consistent Shirley-background subtraction and peak-fitting reveals that the Mn 3s splitting increases systematically with in-plane tensile strain (see Figure 3b). The low value of 4.49 eV is observed for the fully-relaxed bulk-like film (see Figure 3a), consistent with the prior studies and indicating predominantly Mn 4+ ion content [40][41][42] . The high value of 4.64 eV is observed for the maximallystrained (+4.0% tensile) film on the LSAT substrate (see Figure 3a), indicating a significant contribution of the lower-valent Mn 3+ ions, consistent with the XAS results.…”
Section: Textsupporting
confidence: 90%
“…Self-consistent Shirley-background subtraction and peak-fitting reveals that the Mn 3s splitting increases systematically with in-plane tensile strain (see Figure 3b). The low value of 4.49 eV is observed for the fully-relaxed bulk-like film (see Figure 3a), consistent with the prior studies and indicating predominantly Mn 4+ ion content [40][41][42] . The high value of 4.64 eV is observed for the maximallystrained (+4.0% tensile) film on the LSAT substrate (see Figure 3a), indicating a significant contribution of the lower-valent Mn 3+ ions, consistent with the XAS results.…”
Section: Textsupporting
confidence: 90%
“…Nickel possesses one electron in e g orbit in Ni 3+ state, as illustrated in Fig. 4(d This is similar to the scenario reported in the previous publication, 8,[28][29][30] and a further low-temperature XMCD (x-ray magnetic circular dichroism) is expected to give an insight into the respective contribution to magnetism during the transition. But this is not the case for the 3 u.c.…”
supporting
confidence: 67%
“…The elongation of the outof-plane lattice parameters would stabilize the preferred 3z 2r 2 orbit occupancy. [34][35][36] Thus, it is concluded that the strain exerted by a comparatively thick LNO overlayer leads to orbital reconstruction.…”
Section: Resultsmentioning
confidence: 99%